Saint Judy [videorecording (DVD)] - Hanish, Sean; Hanish, Sean; Monaghan, Michelle; Lubany, Leem; Common (Musician) (Blue Fox Entertainment, 2019)
The story of immigration attorney Judy Wood, and her fight to initiate change in asylum law.